Keanekaragaman Olahan Kue Gorengan Berbasis Adonan Cireng - Miftahul Khairani; Amanda Nurul Aisyah Naibaho; Rika Armiati; Nur Holila (Universitas 45 Surabaya, 2024)
Cireng is a simple snack made from flattened and fried reed flour.The term cireng is an abbreviation of fried reeds. This is a chili snack made from tapioca flour, but many also combine it with rice. The characteristic of this cold snack is its chewy texture and delicious taste. This cold snack is made from flat dough and filled with spring onions and carrots. In some cases, variations may depend on personal preference. The aim of this entrepreneurship program is to improve students' business skills and marketing skills of homemade products. Thanks to this entrepreneurship program, we can now sell homemade products and use leftover rice at home.